Importance of Early Childhood Education and Its Impact on Children's Cognitive and Social Development - Dr. Pawan Kumar, (International Journal of Scientific Research in Science and Technology, 2025)
The foundation for a child’s future mental, social and psychological development is created during the important ECE period. Children at this educational stage are usually between the ages of newborn infants and those who are eight decades old. Socializing, learning through play and education that fits the development of a child are part of early childhood education. ECE’s main task is to help children grasp the most important ideas, abilities and knowledge to aid them in school and in life. While in ECE, children pick up important abilities like teamwork, solving challenges, using logic and controlling their emotions. There is proof that students enrolled in top early childhood programs excel in their studies and get along better with others compared to those not in such programs. That is why governments and teachers now see that spending on ECE can help remove inequalities and make all children succeed.
Keywords: Creativity; Preschool Education; Preschool Education Program; Early Childhood Education; PAUD Teachers; Distance Learning; Belajardari Rumah; Covid-19 Pandemic